Pengaruh Brand Ambassador, Brand Image dan Promosi Terhadap Keputusan Pembelian Menantea di Kota Medan - Ayu Cecilia Siahaan; Mbayak Ginting; Litka Tiadora Ria Br Ginting (Fakultas Bisnis Universitas Mikroskil, 2023)
This study aims to determine and analyze the effect of Brand Ambassador, Brand Image and Promotion on Menantea Purchasing Decisions in Medan City. This research uses purposive sampling technique carried out by distributing questionnaires online using google form to 96 samples, namely Menantea consumers in Medan City who have consumed Menantea drinks. The data analysis method used in this study is multiple linear regression. Partial testing (t test) shows that the brand ambassador, brand image and promotion variables affect the Menantea Purchasing Decision in Medan City. Furthermore, the results simultaneously (F test) show that the three independent variables (Brand Ambassador, Brand Image and Promotion) affect the dependent variable (Purchase Decision). Adjusted R2 shows that the Brand Ambassador, Brand Image and Promotion variables can explain the variation in the Purchasing Decision variable by 94,8% and the remaining 5.2% is explained by other factors not examined in this study.